Pengaruh Video Pembelajaran Materi Hati Nurani: Memilih Yang Benar Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas VII SMP Negeri 4 Pahae Julu - Mey Lenna Panggabean; Robinhot Sihombing; Malani Simanungkalit (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The purpose of this research is to determine the effect of learning videos on conscience material: choosing the right on student learning outcomes in Christian Religious Education and Character Education subjects in class VII SMP N 4 Pahae Julu. The research hypothesis is: "There is a positive and significant influence of learning videos on the material of conscience: choosing the right on PAK and Characteristics learning outcomes in class VII of SMP Negeri 4 Pahae Julu, North Tapanuli Regency for the 2023/2024 Academic Year." The population is all students in class VII of SMP Negeri 4 Pahae Julu, totaling 110 people. The research sample was determined purposively, namely 36 students in class VII B as the experimental class who used video and class VII A, totaling 39 people as the control class who did not use video. The research approach uses a true experimental design method (experiment) with a post-test only control group design. The instrument used in this research was a test with 25 questions. Research data for the test questions were analyzed using the Pooled Variance t test formula. From the calculation results, the value of tcount = 6.483 > ttable(α=5%) = 2.000. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a positive and significant influence of learning videos on the material of conscience: choosing the right one on PAK and Characteristics learning outcomes in class VII of SMP Negeri 4 Pahae Julu, North Tapanuli Regency for the 2023/2024 Academic Year. The difference in PAK and Characteristics learning outcomes in class VII of SMP Negeri 4 Pahae Julu, North Tapanuli Regency for the 2023/2024 academic year is known from the average Christian Religious Education learning outcomes for students using learning videos on conscience material: choosing the correct one is 0,79 is higher than the average PAK and Characteristics learning outcomes for students who do not use learning videos on conscience material: choosing the right one, namely 0.67.